Optimization of Eco-Enzyme Utilization for Improving Water Quality of the Badung River in Denpasar - Vonny A Susanta; Edwin Edwin (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to optimize the utilization of eco-enzyme as an environmentally friendly solution to improve the water quality of the Badung River in Denpasar. The program was designed using a participatory approach that involved local communities at all stages, including problem identification, training, implementation, and evaluation. Eco-enzyme was produced from organic household waste such as fruit and vegetable peels through a fermentation process, and subsequently applied to selected points of the river. The results of the program indicate that the application of eco-enzyme contributed to gradual improvements in water quality, particularly in reducing unpleasant odors, decreasing turbidity, and stabilizing pH levels. In addition, the program successfully enhanced community awareness and participation in environmental conservation, as reflected in improved waste management practices and reduced direct disposal of organic waste into the river. The participatory method also fostered a sense of responsibility and sustainability among community members. Despite its positive outcomes, the effectiveness of eco-enzyme application is influenced by factors such as dosage, consistency of use, and the level of existing pollution. Therefore, continuous implementation and community engagement are essential to achieve long-term impact. Overall, this program demonstrates that the use of eco-enzymes can be a practical, low-cost, and sustainable approach to improving urban river water quality.